Investigation of Influences of Secondary butyl-alcohol Blends on Performance and Cycle-To-Cycle Variations in a Spark Ignition Engines - I. M., Yusri; R., Mamat; Azmi, W. H.; Awad, Omar I.; Mohd Hafizil, Mat Yasin; Ahmad Fitri, Yusop (Elsevier Ltd, 2017)
Depletion of fossilised fuels coupled with stringent energy security has directed automotive researches to continuously investigate the use of alternative fuels in internal combustion engines. Within this subject, the research presented in this work is focused on using butanol as gasoline fuels substitution in a spark ignition engines. The present study reveals the combustion analysis specifically on cycle-to-cycle variations in spark ignition engines and performance characteristics of secondary butyl alcohol (sec-butanol) – gasoline blends at 5%, 10% and 15% by volume of sec-butanol in gasoline fuels. The engine performance characteristics was evaluated at 1000 to 4000 RPM with 50% of wide open throttle positions, while the in-cylinder pressure data were collected over 200 consecutive engine cycles for engine test at 3500 RPM. The indicated mean effective pressure time series is analyzed using the coefficient of variations and the wavelet analysis method. Comparative analysis of the performance characteristics showed that 2-butanol–gasoline blended fuel produced less brake power and brake mean effective pressure by 12.3%, 9.2% and 4.3%, for GBu5, GBu10 and GBu15, respectively, with regard to G100. From the wavelet power spectrum, it is observed that the long-term periodicities appear in gasoline fuels, while the short period oscillations become intermittently visible in blended fuels. Reduction of coefficient of variations occur as the additive of sec-butanol ratios increased, which agrees with the wavelet analysis results. Furthermore, the spectral power reduced with an increase in the additive ratio, indicating that the additive has a noticeable influence on reducing the cycle-to-cycle variations.